PENGARUH STRUKTUR MODAL DAN KOMPOSISI ASET TERHADAP KUALITAS LABA PERUSAHAAN JASA TRANSPORTASI DI BURSA EFEK INDONESIA 2012 – 2014 - Fadjar Harimurti, Diah Nurul Khasanah, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
Earning information which owned by the service transportation company will be beneficial for the users of financial statements. The purpose of this study is to determine the effect of capital structure and asset composition on earning quality companies listed on the Indonesia Stock Exchange (IDX) 2012-2014. Method of sampling which used was non probability sampling. The samples are 6 service transportation companies. Analysis of the data in this study using multiple linear regression analysis. To get the unbiased test result, first of all was tested the classical assumptions, then test the feasibility of the model. Capital structure has a positive direction and significant on earning quality while asset composition asset has a negative direction and significant on earning quality.Keywords: capital structure, composition asset, quality of earning